Tinjauan Visual Karakter Death pada Film Animasi “Puss In Boots The Last Wish” - Awal Januardi; Jupriani Jupriani (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
The animated film "Puss in Boots : the Last Wist" is one of the most successful animated films in 2022, this is thanks to the presence of the antagonist, Death, which is the main attraction in this film. The visuals displayed by the antagonist character design have a deep meaning, making it an object of research that can inspire and provide insights related to character creation. The purpose of the research is to analyze the visual meaning of attributes, character types, and gestures as well as the process of creating the main antagonist character "Death" in the animated film "Puss in Boots: the Last Wish". This research uses a descriptive method that will be described by using the manga matrix theory developed by Hiroyoshi Tsukamoto to design new characters with 3 main variables, namely matrix form, matrix costume, and matrix personality. The results of this study show that character creation requires a long process such as determining the basic role and concept of the character, then analyzing references taken from history, myths and folklore related to the character. This element is very important because it will be the beginning of the visual design of the character which is then strengthened by visual depictions through the design of clothes, attributes and weapons used, as well as the giving of personality to the character that makes it more lively. In conclusion, the creation of a character not only requires attractive character visuals, but also covers various aspects that are not few, to produce iconic characters and are liked by the audience.